Implementation of Regional Regulation on Market Management in the Regulation of Morning Market Traders in Relation to Traffic Congestion in the Projo Ambarawa Market Area - Widya Kusumasari; Dani Muhtada Muhtada (Law Research Review Quarterly, 2026)
Traffic congestion in the Projo Ambarawa Market area demonstrates that traffic problems within commercial areas are not solely associated with the increase in vehicle volume, but also with the governance of economic activities and the utilization of road space. This study aims to analyze the implementation of Regional Regulation of Semarang Regency Number 9 of 2024 concerning the Establishment, Arrangement, and Development of People’s Markets in the regulation of Morning Market traders, as well as to assess its effectiveness in relation to traffic congestion in the market area. This research employs an empirical juridical approach by examining normative provisions and their implementation through interviews, field observations, and analysis of relevant legal materials. The findings indicate that the Regional Regulation has been administratively implemented for traders operating within the market area through mechanisms of trader identification, limitation of operational hours, and monitoring by the authorized regional government agencies. However, its effectiveness remains limited because trading activities extend beyond the market boundaries and fall within a fragmented configuration of authority among the Trade Office, the Transportation Agency, the Civil Service Police Unit, and private land managers. Congestion in the area is not only triggered by the presence of traders, but also by the concentration of economic activities, on-street parking practices, public transportation stops outside designated points, and weak cross-sector coordination. This study concludes that the principal issue lies in the governance of authority and coordination that have not been sustainably integrated, such that the effectiveness of congestion control cannot be achieved solely through the normative instruments of the Regional Regulation.